2017
DOI: 10.1016/j.apmr.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Carers' Experiences, Needs, and Preferences During Inpatient Stroke Rehabilitation: A Systematic Review of Qualitative Studies

Abstract: This systematic review provides new insights into the experiences, needs, and preferences of carers of stroke survivors undergoing inpatient rehabilitation. Carers experienced distress as they navigated a foreign culture and environment without adequate communication and processes in place for their inclusion. We recommend deliberate efforts to provide a more inclusive environment that better supports and prepares carers for their new role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 50 publications
6
86
0
4
Order By: Relevance
“…Other studies also support the importance of providing opportunities for independent activities as a way of increasing patient control and promoting feelings of positivity and well‐being . Similar to this current study, another qualitative systematic review reported carers’ distress as they “navigated a foreign culture and environment” and the importance of providing a more inclusive milieu as they prepared to assume a caregiver or supportive role …”
Section: Discussionsupporting
confidence: 81%
“…Other studies also support the importance of providing opportunities for independent activities as a way of increasing patient control and promoting feelings of positivity and well‐being . Similar to this current study, another qualitative systematic review reported carers’ distress as they “navigated a foreign culture and environment” and the importance of providing a more inclusive milieu as they prepared to assume a caregiver or supportive role …”
Section: Discussionsupporting
confidence: 81%
“…They also highlight the significance and complexity of the carer role during transitions between services and in maintaining continuity of care (Ghazzawi et al, 2016;Hvalvik & Reierson, 2015), and associated difficulty for carers when stroke survivors are discharged home. Carers need support (King et al, 2010), particularly with medications (Pindus et al, 2018), as they coordinate services and provide the stroke survivor with instrumental and emotional support (Aziz et al, 2016;Luker et al, 2017). .…”
Section: Discussionmentioning
confidence: 99%
“…They adopt responsibility for managing and coordinating care after the stroke patient is discharged, and frequently feel inadequately prepared to undertake this role (Aziz, Pindus, Mullis, Walter, & Mant, 2016). They need to be included in planning and training for discharge (Pindus et al, 2018), and require resources to initiate services, manage finances, adapt to changes in their relationship with the stroke survivor, and develop coping strategies to adapt to this sudden change in their lives (Luker et al, 2017). In addition, carers need information about stroke associations, support groups, home services, and available community facilities (Pindus et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…La rehabilitación implica un proceso multidisciplinario que gira en torno al paciente, pero que debe contar con la presencia de médicos, enfermeras, fisioterapeutas, trabajadores sociales, terapistas del lenguaje y terapistas ocupacionales, además de los cuidadores en casa que se convierten en el eje fundamental del proceso, pues los familiares son quienes pasan más tiempo con el paciente (51); por esto, es esencial coordinar encuentros desde el primer momento entre el grupo de especialistas y la familia, donde se les instruya y se les entrene en todo lo relacionado con las estrategias a implementar, ya que es claro que, cuando una persona sufre un ECV, esto no solo cambia su vida, sino también la de todos aquellos que la rodean (52,54).…”
Section: Rehabilitaciónunclassified